TAWHID AND THE CRITICISM OF MODERN HUMANISM: Reflection on Alî Sharî’atî’s Thought - Taufik, Zulfan; Taufik, Muhammad (Ulul Albab: Jurnal Studi Islam, 2023)
The rise of modern humanism, with its promise of elevating human dignity through anthropocentrism, has paradoxically contributed to deepening global humanitarian crises. In this context, Islam, as a theocentric (God-centered) worldview, faces the urgent challenge of demonstrating its relevance and adequacy in addressing contemporary human concerns. This article explores the tawḥidic worldview of Alî Sharîʿatî and his critical engagement with modern humanism. Utilizing a qualitative literature review and a descriptive-analytic method, the study examines Sharîʿatî’s primary texts to uncover how his understanding of tawḥid (divine unity) offers a compelling theological alternative to secular humanist paradigms. Sharîʿatî positions tawḥid not only as the central doctrine of Islam but also as a transformative worldview that restores human dignity by re-establishing the vertical relationship between the human and the Divine. In his view, monotheism liberates individuals from subjugation to worldly powers by instilling accountability to a single transcendent authority—God—thereby affirming both human freedom and responsibility. The study argues that Sharîʿatî’s critique of modern humanism— whether in its liberal, Marxist, or existentialist forms—exposes deep contradictions stemming from the philosophical marginalization of the metaphysical. By re-centering the divine in discourse on humanity, Sharîʿatî offers a vision of liberation rooted in spiritual ontology. This research contributes to contemporary Islamic thought and philosophical anthropology by demonstrating how Islamic theology can respond to and critique the failures of modern humanism, offering an ethically grounded framework for addressing today’s pressing humanitarian challenges.